2016
DOI: 10.23849/npafcb6/329.347
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Climate and Competition for Offshore Prey on Growth, Survival, and Reproductive Potential of Coho Salmon in Southeast Alaska

Abstract: This book that contains 38 research articles on marine ecology of Pacific salmon and steelhead trout, is dedicated to the International Year of the Salmon and is the first scientific publication that contributes to the library of the project.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 96 publications
0
10
0
Order By: Relevance
“…Because most of our data come from commercial harvests that occur in ocean-phase fish prior to the development of obvious external secondary sexual characteristics, we did not analyze the sexes separately. However, other studies examining length at age with reliable sex determination have shown similar trends in size and age for males and females 33,59 . As in Lewis et al 19 , we assume our results reflect similar trends in male and female salmon.…”
Section: Methodsmentioning
confidence: 74%
“…Because most of our data come from commercial harvests that occur in ocean-phase fish prior to the development of obvious external secondary sexual characteristics, we did not analyze the sexes separately. However, other studies examining length at age with reliable sex determination have shown similar trends in size and age for males and females 33,59 . As in Lewis et al 19 , we assume our results reflect similar trends in male and female salmon.…”
Section: Methodsmentioning
confidence: 74%
“…The variable survival rates of different sizes of smolting O . kisutch (Lum, ) and the nomadic nature of return spawners (Shaul et al ., ), also may act to limit population sizes.…”
Section: Discussionmentioning
confidence: 99%
“…; Ruggerone et al. ; Shaul and Geiger ). For example, length of age‐1.4 Chinook Salmon from six Alaskan stocks was negatively correlated with Pink Salmon abundance in 1983–2012 (average r = −0.55, P < 0.05; G. Ruggerone, unpublished analysis).…”
Section: Discussionmentioning
confidence: 99%